Al-wasaṭiyyah: the path to success - Nuhu, Ibrahim; Gapur, Oziev (IIUM Press, 2020)
The Ummah of Islam is experiencing a wide spectrum of difficulties, threats, and internal breakdown that is based mainly on negative behaviors e.g. extremism and alike. The unity and brotherhood amongst the members of the Muslim communities is either weak or does not exist anymore. The Ummah is broken into sects and groups where every group is labeling the others with all sorts of names. Concerning the matter of Iqtiṣād (economics) backwardness is observed in many parts of the Muslim world. The Al-Iqtiṣād Al-Islamī (Islamic economics) is based on earning and spending ḥalāl wealth in the correct manner. Both actions have to be well managed in order to create a sustainable society. This is contrary to the currently popular materialism that has led the world into a culture of excessiveness in spending and consumption. Subsequently this has increased the amount of debt owed by individuals, business and governments. An alarming trend is that there is minimal concern about attaining wealth through ḥalāl means and sources of ḥarām income are on the rise. Consequently, there has been a decrease of blessings in wealth and contentment regardless of the magnitude of one’s wealth. Thus, observing al-Wasaṭiyyah is highly encouraged and appreciated by the Sharīʿah in all circumstances. This paper addresses the guidelines given by the Qurʾān and Sunnah on al-Wasaṭiyyah and its importance in building a sustainable economy and society. The paper is mainly based on the revealed texts that address the above stated issues directly or indirectly.